Analisis Kemampuan Spasial Matematika Siswa SMP Pada Materi Bangun Ruang Sisi Datar - Ummu Qo'is; Teguh Wibowo; Wharyanti Ika Purwaningsih (Jurnal Inovasi Pendidikan Matematika (JIPM), 2021)
This research is describing the spatial mathematical abilities needed by junior high school students specifically on polyhedron material. This type of research is a qualitative descriptive study. The subjects of this study were 3 students of class IX grade students of State Junior High School 4 Purworejo in the 2019/2020 academic year who had already gotten material on three-dimentional figure and had high mathematical abilities, moderate mathematical abilities, and low mathematical abilities and were in accordance with the needs of the relevant teachers . The subject taking technique used in this study was purposive. The instrument used in this study was the spatial ability test sheet. Data collection uses spatial ability tests, field notes, and interviews. The data analysis technique used is the analysis technique of Miles & Hubermen which includes three activities namely data reduction, data presentation, and the contribution of conclusions. Based on the results of the analysis found students with high mathematical abilities are able to bring up spatial perception, mental rotation, spatial relations, and spatial orientation, but have not been able to bring up spatial visualization. Students with moderate and low mathematical abilities are able to bring up spatial perception, mental rotation and spatial orientation but have not yet spawned spatial relations and spatial visualization.